(untitled) (GEOmedia, 2018)
Ground movements can cause damage around buried pipes and infrastructures. Satellite radar technology can give a good predictive indicator for where this may be occurring, helping utility companies face the complex and expensive task of the maintenance of underground pipelines. Rheticus Network Alert is a turnkey cloud-based service that processes satellite imagery and geospatial data automatically to deliver geo-information services, helping utility companies in the management of inspections and maintenance activities over their integrated water and sewerage networks. Hera Group decided to start using Rheticus system over the Provinces of Modena and Bologna, Italy, with the aim of providing an automatic system to exploit satellite data in order to perform complex analyses, and simplify inspection planning.